Community Structure of Macrozoobenthos in Mangrove Ecosystem, Kutai National Park, East Kalimantan - Anugrah A Budiarsa; Samsul Rizal (International Journal of Science and Engineering, 2014)
Mangrove forest in Kutai National Park (KNP) is considered as nature-protected ecosystem. This forest ecosystem has high productivity ecosystem roles as feeding source, spawning and conservation area for water organism living in this surrounding area such as fishes, crustacean, mollusk and others. At the mangrove floor, mangrove is a benthic ecosystem that utilizes organic material either produced from mangrove itself or land sedimentation. This research was conducted using quadrant transect method with 10 observation stations. Collected data were identified, summed and analyzed. Community structure was analyzed by determining the diversity index, homogenous index and dominant index. The research showed that Makrozoobenthos found at the research location was 17 species which divided into 12 families and 3 classes. The smallest number was found in Lombok Bay (station number 8) with 6 species. The largest number was found in Perancis Cape (station number 9) with 15 species. The diversity index of community structure ranged from 1,7 to 2,4. This indicated that the community diversity was at moderate level (1,5<N<3) with good homogenous index 0,8-1